Effect of soldering condition on formation of intermetallic phases developed between Sn-0.3Ag-0.7Cu low-silver lead-free solder and Cu substrate - Mookam, Niwat; Kanlayasiri, Kannachai (My University, 2011)
In this paper, effect of soldering time and temperature on formation of intermetallic compounds developed between Sn-0.3Ag-0.7Cu lead-free solder and copper substrate was investigated. Dip soldering was performed at 250, 270, and 290 °C with soldering time of 5, 10, 15, and 20 s. Either ε-Cu 3Sn or η-Cu6Sn5 intermetallic phase was found at the interface between the solder and the substrate depending on the soldering condition, i.e., soldering time and soldering temperature. ε-Cu3Sn was found only when the substrate was soldered at 250 °C for 5 and 10 s. At other soldering conditions, only η-Cu 6Sn5 was found at the interfacial zone. Crystal structure of ε-Cu3Sn intermetallic phase was orthorhombic, and it was hexagonal structure for η-Cu6Sn5. Transformation of the intermetallic phases was also discussed. © 2011 Elsevier B.V. All rights reserved.
Keywords: Intermetallics; Mechanical properties; Metals and alloys; Microstructure